Research on organizing spatial production of economic models for agro - fisheries and Processing industry in Diem Dien Town, Thai Thuy District, Thai Binh Province - Thanh, Dinh Van; Ha, Le Van (VNU Journal of Science: Earth and Environmental Sciences, 2008)
Abstract